2014
DOI: 10.1128/aem.00175-14
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Insertions in the Lactobacillus casei upp Gene That Are Useful for Vaccine Expression

Abstract: bTo develop a stable and marker-free Lactobacillus strain useful for the expression of vaccines, we developed a temperature-sensitive suicide plasmid with expression cassettes containing an HCE promoter, a PgsA anchor, the alpha-toxin gene, and an rrnB T1T2 terminator (PP␣T) that uses a 5-fluorouracil (5-FU) counterselectable marker for Lactobacillus casei. Three strains containing the correct PP␣T expression cassettes were produced via the selective pressure of 5-FU screening. We confirmed that the upp gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…The constitutive expression plasmid pPG‐T7 g10‐PPT, containing an HCE promoter, T7g10 enhancer, PgsA anchor and the rrnBT1T2 terminator, was constructed in our laboratory (Song et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The constitutive expression plasmid pPG‐T7 g10‐PPT, containing an HCE promoter, T7g10 enhancer, PgsA anchor and the rrnBT1T2 terminator, was constructed in our laboratory (Song et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…After that, the COE-Col-DCpep fusion genes were cloned into the expression plasmid pPG-T7g10-PPT, to generate pPG-T7g10-PPT-COE-Col-DCpep. To construct the recombinant lactobacillus strains, the recombinant plasmids were electrotransferred into L. casei 393 as described previously [25], giving rise to the recombinant strain pPG-COE-Col-DCpep/L393. In addition, pPG-T7g10-PPT-COE/L393, pPG-T7g10-PPT-COE-Col/L393 and pPG-T7g10-PPT-COE-DCpep/L393 were also generated and maintained in our laboratory.…”
Section: Construction Of Recombinant Lactobacillus Strainsmentioning
confidence: 99%
“…One of the most exploited N-terminal transmembrane helix anchors is the PgsA protein from Bacillus subtilis, which is part of the poly-γ-glutamate synthetase complex. Several reports describe coupling of antigens to the C-terminus of PgsA, leading to successful surface display in L. casei and L. lactis [12,33,[49][50][51][52][53][54]. In these studies, surface-display was confirmed using fluorescence microscopy or flow cytometry.…”
Section: N-terminal Transmembrane Anchorsmentioning
confidence: 99%